A revision of the subgenus Bessobates of the genus Netelia from Japan (Hymenoptera, Ichneumonidae, Tryphoninae) - Konishi, Kazuhiko (Zootaxa, 2014)
Japanese species of the genus Netelia of the subgenus Bessobates are revised. Fourteen species are recognized. Four new species, N. (B.) longipad, N. (B.) nigridorsalis, N. (B.) nodai and N. (B.) yakushimensis, are described. Six species, N. (B.) comitor Tolkanitz, 1974, N. (B.) frenata Tolkanitz, 1981, N. (B.) gansuana (Kokujev, 1906), N. (B.) kiuhabona (Uchida, 1928), N. (B.) nanaki Kaur & Jonathan, 1979 and N. (B.) pallescens (Schmiedeknecht, 1910) are recorded from Japan for the first time and redescribed based on Japanese specimens. Male genitalia of N. (B.) yamatoensis (Uchida, 1934) are figured and described for the first time. Netelia (Bessobates) odaiensis (Uchida, 1934) is removed from synonym with virgata and treated as species incertae sedis. Three species, N. (B.) cristata (Thomson, 1888), N. (B.) latungula (Thomson, 1888) and N. (B.) virgata (Geoffroy, 1785) are redescribed based on Japanese specimens. A key to 14 Japanese species is given.